Measuring client experiences in long-term care in the Netherlands: a pilot study with the Consumer Quality Index Long-term Care - Kool Rudolf B; Winters Sjenny; Triemstra Mattanja; Wiegers Therese A (BMC, 2010)
Abstract Background This study aims to describe the development, testing and optimization of a new standard instrument, the Consumer Quality Index (CQ-index®) Long-term Care, for measuring client experiences with long-term care in the Netherlands. Methods Three versions of the CQ-index questionnaires and protocols for study sampling and data collection were developed, designed for interviews with residents of nursing or residential care homes and postal surveys among representatives of psychogeriatric residents and homecare clients. From July to November 2006 a pilot study was conducted among 2,697 clients of 68 nursing or residential care homes, 2,164 representatives of clients in 57 psychogeriatric care institutions, and 1,462 clients of 19 homecare organizations. We performed psychometric analyses and descriptive analyses, and evaluated the pilot study. Results The pilot study showed the feasibility and usability of the instruments, supported the multidimensionality of the questionnaires and showed first findings on client experiences and possibilities for quality improvement. Nine scales applied to all care settings: shared decision making, attitude and courtesy, information, body care, competence and safety of care, activities, autonomy, mental well-being, and availability of personnel. The pilot resulted in three optimized questionnaires and recommendations for nationwide implementation. Conclusions The CQ-index® Long-term Care provides a good basis to investigate the quality of nursing homes, residential care homes and homecare from the clients' perspective. This standardized instrument enables a nationwide comparison of the quality of long-term care for the purpose of transparency and quality assurance.